Right lateral position can improving oxygen saturation and respiratory rate on under-five children with pneumonia - Novita Agustina; Nani Nurhaeni; Happy Hayati (PAGEPress Publications, 2021)
Pediatric patients with pneumonia experience respiratory distress in the form of shortness of breath and rapid breathing, which affects oxygen saturation. Oxygen saturation and respiratory rate can be increased by providing the right lateral position. Fulfillment of oxygen will affect the healing of children and can reduce the length of stay in hospital. The purpose of this study was to identify the effect of right lateral positioning on oxygen saturation and respiratory rate in under-five children with pneumonia. The study design was a quasi-experimental pre-posttest with control group design. Respondents were 32 infants with pneumonia, (right lateral=16 and control group=16), selected by consecutive sampling. Univariate and bivariate analyzes were performed. There was a significant difference in oxygen saturation before and after right lateral position (p-value=0.000) and there was a significant difference in the respiratory rate before and after right lateral position (p-value=0.000). The results can be used to improve health services by promoting the right lateral position as a selftreatment intervention for increasing oxygen saturation and stabilizing respiratory rate in infants with pneumonia.